Analisis Status Mutu Perairan Pelabuhan Belawan Medan Berdasarkan Indeks STORET dan Indeks Pencemaran - Yolanda, Yuni (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Belawan Harbor of North Sumatra is the third-busiest seaport in Indonesia and a gateway to the economic activity in the respective area. This study aimed to analyze the harbor water quality status and its sources of pollution. The data used for this study was the secondary data from the book of harbor environmental management and observations in 2015-2018 and the governmental regulation number 22 of 2021 on the harbor water quality standards. The observation was conducted in 14 different stations. The data obtained was then analyzed using STORET and pollution index to determine the quality status then using Pearson correlation to correlate the data. The results showed that according to the pollution index method, the water in Belawan Harbor is categorized as in good condition (comply with the water standard). However, according to the STORET method, the harbor water quality status is in mild pollution categories. The ocean fishing harbor of Belawan (station 7) and Deli estuary (station 8) have the highest number of pollutants. Overall, the water status in the harbor of Belawan is within the threshold of the designated water standard. The polluted conditions generated from anthropogenic activity such as industrial, fishing and agriculture activity and also affected by the geographical location of the habor which located in the estuary area. In addition, the temperature, turbidity, and salinity are the main factors affecting the water ecosystem in Belawan Harbor.